Sosialisasi Pentingnya Peran Orang Tua dan Keterlibatan Ayah Terhadap Anak di Kelurahan Kalijudan. - Adhis Haifa Lestari Je Musron; Andini Chaerania; Noviana Safira; Rinaldi Fransius Simbolon (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Socialization regarding the importance of the role of parents and the involvement of fathers in children is one of the efforts made to change the mindset of the people of Kalijudan Village. It is hoped that this socialization activity can open views and provide insight into the importance of the role of parents in child development, as well as provide encouragement for fathers to be actively involved in child care. The methods used are the presentation method, discussion method and question and answer method. During the socialization, residents were very active in asking questions and the responses were quite satisfactory. Residents and parents show growing understanding and appreciation of the importance of the role of parents in the development of a child's personality, especially the role of fathers, which is very important in shaping children's character.